A 15‐Year Comparative Prospective Study of Surgical and Prosthetic Care and Aftercare of Overdenture Treatment in the Atrophied Mandible: Augmentation Versus Nonaugmentation. (16th December 2015) - Visser, Anita; Stellingsma, Cornelis; Raghoebar, Gerry M; Meijer, Henny JA; Vissink, Arjan
Abstract: Background: Different treatment strategies for the atrophied mandible are described in literature. The need for long term care and aftercare for these strategies is sparsely described, however. Purpose: To prospectively assess the need for prosthetic and surgical care and aftercare of two implant treatment strategies for the atrophied mandible. Materials and Methods: Forty edentulous elderly patients were randomly assigned according to a balanced allocation method to a treatment strategy: dental implants in combination with an augmentation procedure versus a nonaugmentation procedure. All surgical and prosthetic care and aftercare were scored from the first visit until 15 years after implant placement. Results: Twenty elderly patients completed the 15‐year follow‐up. As expected, the augmentation group needed significantly more surgical time than the nonaugmentation group (338 vs 145 minutes), but the need for prosthetic care and surgical/prosthetic aftercare was comparable. Implant survival was lower in augmented mandibles (88.7% vs 98.7%, p  < .05). Aftercare mainly consisted of routine inspections; the need for prosthetic adjustments was minor. Surgical aftercare was hardly needed. Conclusion: The only difference in the need for surgical and prosthetic (after) care was the extra time needed for performing augmentation surgery and the higher risk on implant loss in augmented mandibles. Otherwise, the need for care and aftercare was of the same magnitude. Thus, when applicable, nonaugmentation surgery is preferred as no general anesthesia is needed and the morbidity is low.